Evaluation of DNA methylation status of toll‐like receptors 2 and 4 promoters in Behcet's disease. (12th June 2020) - Kolahi, Sousan; Rashtchizadeh, Nadereh; Mahdavi, Aida Malek; Farhadi, Jafar; Khabbazi, Alireza; Sakhinia, Ebrahim; Bahavarnia, Neda; Farajzadeh Polsangi, Mohammad Jahed; Babaloo, Zohreh; Estiar, Mehrdad A.
Abstract: Background: Altered innate immune function plays an important role in the initiation of inflammatory response in Behcet's disease (BD). Toll‐like receptors (TLRs) are the master regulators of the innate immune system. Because the role of TLRs remains unknown in the pathogenesis of BD, the present study aimed to evaluate the expression levels and methylation status of the TLR2 and TLR4 promoters in patients with BD. Methods: In the present study, Iranian Azeri BD patients ( n = 47) with an active ( n = 22) and inactive ( n = 25) period, and healthy controls ( n = 61), were matched according to age, sex and ethnicity. TLR2 and TLR4 genes promoter CpG islands were predicted with the Eukaryotic Promoter Database (https://epd.vital‐it.ch). Methylated DNA immunoprecipitation (MeDIP) was conducted. Results: The results showed that mRNA of TLR4 was significantly increased in the peripheral blood mononuclear cells (PBMCs) of BD patients with an active phase compared to the control group. Differences in mRNA of TLR4 between the inactive BD and control groups were not significant. Differences in TLR2 mRNA levels in the PBMCs of the active and inactive phase BD and control groups were not significant. The methylation rate of TLR4 gene promoter was significantly lower in the active and inactive BD groups compared to the control group. The difference between the active and inactive BD groups was not significant. There was no significant difference in the methylation rates of the TLR2 gene between studied groups. Conclusions: Our preliminary findings suggest that the hypomethylation of TLR4 gene may be involved in the pathogenesis of BD via increasing TLR4 expression.